Synergistic Neuroprotective Effects of Two Herbal Ingredients via CREB-Dependent Pathway - Liu, Xu; Wang, Dongxiao; Zhao, Runqing; Dong, Xianzhe; Hu, Yuan; Liu, Ping (Frontiers in Pharmacology, 2016)
As two natural oligosaccharide esters, 3,6’-Disinapoyl sucrose (DISS) and tenuifolisideA (TFSA) are originating from the root of Polygala tenuifolia Willd, a traditional Chinese medicine used in treatment of mental disorders. Previous reports have shown that both of them possess in vitro neuroprotective effects by stimulating different upstream pathways related with cyclic AMP-responsive element-binding protein (CREB). In the present study, we investigated the additive neuroprotective effects of DISS and TFSA on Glu-induced damage of SY5Y cells and purposed the possible underlying mechanism. The interaction between DISS and TFSA showed a clear-cut synergistic effect as evidenced by combination index (CI). Additional evidence from biochemical (NOS activity) assays confirmed their additive inhibition on the Glu-induced NOS hyperactivation. Moreover, we showed that co-treatment of DISS and TFSA resulted in an additively up-regulated phosphorylation of CREB as well as increased expressions of CRTC1 and BDNF. Neuroprotective effects of DISS and TFSA on Glu-induced decrease in cell viability were blocked by MAPK/ERK1/2 inhibitor (U0126) and PI3-K inhibitor (LY290042). Nevertheless, the CRTC1 or BDNF expression induced by these two compounds was significantly reduced in the presence of either ERK or PI3-K inhibitor, indicating that the two oligosaccharide esters shared some common pathways in the regulation of CREB-BDNF pathway. Taken together, we, for the first time, showed that DISS and TFSA exerted the additive neuroprotective effects on CREB-BDNF signaling pathway through complementary mechanisms.